Improved 6‐year overall survival in AT/RT – results of the registry study Rhabdoid 2007. (26th May 2016) - Bartelheim, Kerstin; Nemes, Karolina; Seeringer, Angela; Kerl, Kornelius; Buechner, Jochen; Boos, Joachim; Graf, Norbert; Dürken, Matthias; Gerss, Joachim; Hasselblatt, Martin; Kortmann, Rolf‐Dieter; Teichert von Luettichau, Irene; et al.
Abstract : Atypical teratoid rhabdoid tumors (AT/RT) remain enigmatic tumors with no current standard of therapy. Long‐term survival data on consistently treated patients are missing. Our study provides improved long‐term survival data and lays the foundation for future phase I/II clinical trials. It demonstrates the feasibility of generating high‐quality evidence by employing a registry trial. Abstract: Atypical teratoid rhabdoid tumors (AT/RT) are characterized by mutations and subsequent inactivation of SMARCB1 ( INI1, hSNF5 ), a predilection for very young children and an unfavorable outcome. The European Registry for rhabdoid tumors (EU‐RHAB) was established to generate a common European database and to establish a standardized treatment regimen as the basis for phase I/II trials. Thus, genetic analyses, neuropathologic and radiologic diagnoses, and a consensus treatment regimen were prospectively evaluated. From 2005 to 2009, 31 patients with AT/RT from four countries were recruited into the registry study Rhabdoid 2007 and treated with systemic and intraventricular chemotherapy. Eight patients received high‐dose chemotherapy, 23 radiotherapy, and 17 maintenance therapy. Reference evaluations were performed in 64% (genetic analyses, FISH, MLPA, sequencing) up to 97% (neuropathology, INI1 stain). Germ‐line mutations (GLM) were detected in 6/21 patients. Prolonged overall survival was associated with age above 3 years, radiotherapy and achievement of a complete remission. 6‐year overall and event‐free survival rates were 46% (±0.10) and 45% (±0.09), respectively. Serious adverse events and one treatment‐related death due to insufficiency of a ventriculo peritoneal shunt (VP‐shunt) and consecutive herniation were noted. Acquisition of standardized data including reference diagnosis and a standard treatment schedule improved data quality along with a survival benefit. Treatment was feasible with significant but manageable toxicity. Although our analysis is biased due to heterogeneous adherence to therapy, EU‐RHAB provides the best available basis for phase I/II clinical trials.